2010
DOI: 10.1007/s10827-010-0222-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of firing frequency in a computational model of a midbrain dopaminergic neuron

Abstract: Dopaminergic (DA) neurons of the mammalian midbrain exhibit unusually low firing frequencies in vitro. Furthermore, injection of depolarizing current induces depolarization block before high frequencies are achieved. The maximum steady and transient rates are about 10 and 20 Hz, respectively, despite the ability of these neurons to generate bursts at higher frequencies in vivo. We use a three-compartment model calibrated to reproduce DA neuron responses to several pharmacological manipulations to uncover mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 54 publications
4
87
0
Order By: Relevance
“…The sensitivity of Type I behavior is observed experimentally and numerically. g s and its associated membrane current must be small throughout the AHP region, and this is, in fact, seen in precise and difficult biophysical experiments (31) as well as detailed modeling studies (32). Furthermore, increasing I A in the Type II* regime of the ConnorStevens model will only serve to exacerbate the jump to high minimum firing frequency and can never linearize the FI curve.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of Type I behavior is observed experimentally and numerically. g s and its associated membrane current must be small throughout the AHP region, and this is, in fact, seen in precise and difficult biophysical experiments (31) as well as detailed modeling studies (32). Furthermore, increasing I A in the Type II* regime of the ConnorStevens model will only serve to exacerbate the jump to high minimum firing frequency and can never linearize the FI curve.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, Type I behavior is essential in neural circuits that encode information in firing rate (14), or in situations where slow pacemaking is important physiologically (32,50). The fact that Type I is a bounded and sometimes small region in parameter space presents a potential regulation problem for a neuron that has only a few different membrane currents.…”
Section: Ion Channels Have Paradoxical Effects On Excitability In Difmentioning
confidence: 99%
“…Depolarizing current steps elicit steady firing rates up to 10 Hz, and additional depolarization causes a cessation of spiking, although transients as fast as 30 Hz have been evoked by current steps (Blythe et al 2009). Our previous modeling work (Kuznetsova et al 2010) and experimental studies (Deister et al 2009) suggested that the failure to recover from sodium channel inactivation between spikes was responsible for entry into depolarization block and predicted that increasing the availability of sodium channels would delay entry into depolarization block. Subsequently, we showed that decreasing the sodium conductance pharmacologically causes dopamine neurons to go into depolarization block with lower maximal frequencies at lower values of applied current, whereas augmenting this conductance with the dynamic clamp has the opposite effect .…”
mentioning
confidence: 99%
“…Also, various manipulations in vitro (Deister et al 2009;Ji et al 2012;Ping and Shepard 1996;Yu et al 2014) can evoke a train of action potentials of variable frequency prior to entering depolarization block. Previous models (Drion et al 2011;Kuznetsova et al 2010;Oster and Gutkin 2011) do not capture critical aspects of the firing rate limitation and how it is circumvented. Therefore we examined depolarization block in a simple model that faithfully reproduces the sodium current measured in these neurons (Seutin and Engel 2010) and also in a model with an additional slow component of sodium channel inactivation, recently observed in these neurons (Ding et al 2011).…”
mentioning
confidence: 99%
“…Depolarization block is regarded to have pathological relevance for some brain disorders, including epilepsy and schizophrenia [32][33][34] . Among all the mechanisms known to cause depolarization block, the inactivation of voltage-dependent Na + channels is believed to play a key role [31,35,36] . SKF83959 can decrease the amplitude of Na + currents [17] ; however, whether the drug has an effect on the depolarization block of pyramidal neurons in the hippocampus remains to be determined.…”
Section: Introductionmentioning
confidence: 99%